Isothermal amplification coupled with rapid flow-through hybridisation for sensitive diagnosis of Plum pox virus - Olmos, Antonio; Bertolini, Edson; Cambra, Mariano (2017)
A nucleic acid sequence-based amplification method Coupled with rapid flow-through hybridisation (NASBA-FH) was developed for diagnosis of Plum pox virus (PPV). The sensitivity level achieved by NASBA-FH was 10 times higher than that obtained by Co-PCR and 1000 times higher than the sensitivity afforded by RT-PCR. In addition, samples from 262 stone-fruit trees collected during winter and spring seasons were analysed. These samples were tested using methods recommended by the European and Mediterranean Plant Protection Organization to detect PPV (DASI-ELISA, RT-PCR and Co-PCR) and by NASBA-FH. Winter PPV diagnostic results by ELISA and NASBA-FH coincided in 90.8%, while ELISA and PCR-based methods coincided in 91.6% and PCR-based methods with NASBA-FH agreed in 95.4%. In spring, diagnostic results were similar with all the molecular techniques, which agreed with ELISA results for 98.8% of the trees. NASBA-FH was able to detect more positive infections in winter, which were later confirmed in spring. These results indicate that NASBA-FH is a suitable molecular method for routine PPV detection in the winter and spring. This user-friendly isothermal RNA amplification coupled with a very fast flow-through hybridisation (15 min) opens up new possibilities for rapid and reliable diagnosis of a variety of pathogens. (c) 2006 Elsevier B.V. All rights reserved.